Awareness of Type 1 DM Patients about the Importance of Carbohydrate Counting and Insulin Corrective Factor in Tabuk Region, KSA 2025 - Albalawi, Ahmad Raja Saeed; Alharbi, Asma Ali; Alfaer, Sarah Abdulleh; Alharbi, Amal Ali; Alanizi, Areej Daham (Journal of Neonatal Surgery, 2025)
Background: T1DM is a disabling chronic condition that necessitates functional approaches like CC and insulin corrective factors to achieve successful diabetes Self-Management. Thus, the degree of knowledge and usage of these practices by the T1DM patients in Tabuk, Saudi Arabia, has not been determined yet. Objective: The objective of the present investigation was to evaluate the level of patients’ knowledge about T1DM, CC and insulin corrective factors and to determine the prevalence and demographic and clinical characteristics of patients with inadequate knowledge or suboptimal practice. Methodology: This work involved descriptive cross-sectional research and was done in Tabuk, Saudi Arabia within July-December 2024. In this cross-sectional study, 428 T1DM patients with age ≥18 from primary care clinics participated in this study based on convenience sampling. Data was obtained through interview administered questionnaires and analyzed with the assistance of statistical package for the social science (SPSS) version 26. Quantitative data was summarized using descriptive statistics while inferential statistics in form of chi-square tests were used to determine if there was significant association between two variables, at a significance level of 0.05. Results: Out of all respondents 66% displayed awareness of carbohydrate counting methods yet only 22% put this knowledge into practice to manage their diabetes. The research showed that 93% of participants understood insulin correction factors. A higher level of education paired with continued dietitian consultations and shorter diabetes duration (less than 10 years) contributed to better awareness of the disease (288 respondents respectively). Out of 167 respondents who lacked diabetes knowledge approximately half (55 people) experienced inadequate glucose levels accordingly. Survey results demonstrated that high blood sugar frequency (HbA1c > 8.0%) affected 290 of the respondents. Conclusion: The results suggest low knowledge and poor adherence to CC of insulin correction factors among 1TDM patients in Tabuk. This gap means that there is need to conduct more educational interventional targeted at ensuring that patients with diabetes have adequate knowledge and practice these crucial diabetes self-management behaviors. Glycemic control awareness and daily practice can help reduce complications, thus improving the life span of individual with T1DM.